2021
DOI: 10.1177/15330338211033061
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Diagnostic Accuracy of Let-7 Family for Cancer: A Meta-Analysis

Abstract: Background: Cancer is a global public health problem affecting human health. Early stage of cancer diagnosis, when it is not too large and has not spread is important for successful treatment. Many researchers have proposed that the let-7 microRNA family can be used as a biomarker for cancer diagnosis. The aim of this meta-analysis is to evaluate whether let-7 family can be used as a diagnostic tool for cancer patients. Methods: We conducted a comprehensive literature search on PubMed, EMBASE, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Based on the titles and abstracts, 50 articles were left for full-text evaluation. Finally, 28 articles were excluded, and 22 meta-analysis articles ( Liu et al, 2014a ; Wang et al, 2014c ; Xin et al, 2014 ; Shen et al, 2015b ; Cui et al, 2015 ; Gao et al, 2016a ; Gao et al, 2016b ; Hou et al, 2016 ; Li et al, 2016 ; Xie et al, 2016 ; Imani et al, 2017 ; Tang et al, 2017 ; Xin et al, 2017 ; Cai et al, 2018 ; Yu et al, 2018 ; Wang et al, 2019c ; Jiang et al, 2020 ; Zhao et al, 2020 ; Liu et al, 2021a ; Liu et al, 2021b ; Zhang et al, 2021 ) were extracted for further analysis. Among which, 30 datasets were obtained, and subsequently, two miRNAs were selected as the most frequent ncRNAs that have been assessed as a non-invasive biomarker in systematic reviews and meta-analysis studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the titles and abstracts, 50 articles were left for full-text evaluation. Finally, 28 articles were excluded, and 22 meta-analysis articles ( Liu et al, 2014a ; Wang et al, 2014c ; Xin et al, 2014 ; Shen et al, 2015b ; Cui et al, 2015 ; Gao et al, 2016a ; Gao et al, 2016b ; Hou et al, 2016 ; Li et al, 2016 ; Xie et al, 2016 ; Imani et al, 2017 ; Tang et al, 2017 ; Xin et al, 2017 ; Cai et al, 2018 ; Yu et al, 2018 ; Wang et al, 2019c ; Jiang et al, 2020 ; Zhao et al, 2020 ; Liu et al, 2021a ; Liu et al, 2021b ; Zhang et al, 2021 ) were extracted for further analysis. Among which, 30 datasets were obtained, and subsequently, two miRNAs were selected as the most frequent ncRNAs that have been assessed as a non-invasive biomarker in systematic reviews and meta-analysis studies.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included articles are shown in Supplementary Table S10 ( Liu et al, 2014a ; Wang et al, 2014c ; Xin et al, 2014 ; Shen et al, 2015b ; Cui et al, 2015 ; Gao et al, 2016a ; Gao et al, 2016b ; Hou et al, 2016 ; Li et al, 2016 ; Imani et al, 2017 ; Xin et al, 2017 ; Cai et al, 2018 ; Yu et al, 2018 ; Wang et al, 2019c ; Zhao et al, 2020 ; Liu et al, 2021b ; Zhang et al, 2021 ). The total number of patients and healthy individuals in these 30 databases was 28,765 and 17,254, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They are generally thought to act as tumor suppressors, regulating the expression of oncogenes (e.g., RAS ) to reduce cancer aggressiveness; however, the situation is uncertain due to conflicting data revealing both their down-regulation and up-regulation in different types of cancer. It has been reported that in rare situations let-7 acts as an oncogene, increasing cancer migration, invasion, chemoresistance, and the expression of genes associated with progression and metastasis [ 32 , 33 ]. For example, Ma et al demonstrated that let-7e is overexpressed and positively affects migration and invasion of esophageal squamous cell carcinoma cells, possibly via targeting ARID3a [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Let-7 family shows potential as a non-invasive marker for cancer diagnosis [ 237 ]. Lower serum miR-let-7a expression has been strongly associated with poor prognosis and efficacy of radiotherapy in lung cancer brain metastasis [ 238 ].…”
Section: Tumor Suppressor Mirnamentioning
confidence: 99%